Triptycenyl‐phenazino‐thiadiazole as acceptor in organic bulk-heterojunction solar cells - Leibold, David; Lami, Vincent; Hofstetter, Yvonne J.; Becker-Koch, David; Weu, Andreas; Paulus, Fabian; Bunz, Uwe H. F.; Vaynzof, Yana (Organic electronics, 2018)
Herein, we investigate the use of a triptycenyl‐phenazino-thiadiazole as an electron acceptor in solution-processed organic bulk-heterojunction solar cells. We characterize the optoelectronic properties of the acceptor molecule and examine its performance with three different donor polymers. We find that blends with PTB7 show the highest performance reaching a power conversion efficiency of 2.4%. Investigations of 1,8-diiodooctane (DIO) as an additive resulted in only a minor increase in performance (∼10%), suggesting that additives allow rather insignificant control over the blend microstructure. Using transient absorption spectroscopy we identify the loss mechanisms in the device and propose routes to enhance the performance further.
Gesehen am 26.02.2020